Psychometric properties of AMAS and math anxiety prevalence among Chinese and Russian schoolchildren: a comparative study - Du Linna; Wang Xinghua; Yu Haiying; Anna Pavlova; Victoria Ismatullina; Artem Malykh; Pavel Kolyasnikov; Sergey Malykh (Frontiers in Psychology)
The purpose of this study was to compare the prevalence of math anxiety in Russian and Chinese schoolchildren across genders and ages. The Abbreviated Math Anxiety Scale (AMAS) was used as a measurement tool for assessing math anxiety. The factor structure of the AMAS and item invariance between Russian and Chinese schoolchildren were also examined. A total of 4,292 Russian (54% girls, M = 13.7, SD = 1.21) and 3,410 Chinese (48% girls, M = 12.7, SD = 1.21, Me = 13.0) schoolchildren participated in the study. The bi-factor model of the AMAS fits provided the best fit for the data in both countries. AMAS items demonstrated invariance between the two groups. Overall, Russian schoolchildren demonstrated higher math anxiety across all ages and math anxiety subscales, except at ages 14–15, where Chinese schoolchildren reported higher learning-related math anxiety. Among Chinese schoolchildren, both learning and evaluation math anxiety increased with age. Conversely, for Russian schoolchildren, math evaluation anxiety increased, while learning math anxiety decreased with age. Gender differences were observed in both countries, with the onset of gender-related differences appearing earlier in Chinese schoolchildren.